Responses of the Indian Men & Women toward Sex Role Portrayals in Indian Commercials: A Mixed-methods Study - -, Gitanjali (2012)
Sex role portrayals in commercials are an extensively researched domain. Findings of many research studies (e.g. Belkaoui & Belkaoui, 1976; Busby, 1975; Wolin, 2003; Courtney & Lockeretz, 1971; Stern, 1999) confirm that women are often portrayed more stereotypically than men in commercials and that female responses on the same are more condemning than the male responses. This study will extend the work of Lundstrom and Sciglimpaglia (1977), applying it from an Indian context. Therefore, it will aim to study the attitudes of Indian men and women towards sex role portrayals in Indian commercials. The study will employ a triangulation framework, combining quantitative and qualitative research methods. An Internet survey for quantitative analysis and in-depth Skype interviews for qualitative analysis was carried out simultaneously and analysed independently. Responses of males and females were gathered on sex role perceptions, its link with buying intentions and company image. 453 respondents completed the survey and Mann-Whitney U tests using SPSS were carried out for data analysis. Likewise, 22 participants were interviewed through Skype and the information gathered was evaluated using the techniques of horizontalization of data. After integrating the results, it was found that (1) sex role portrayals exist in India and is a serious issue, (2) female portrayals gathered more negative responses than male portrayals (3) the responses of women were more negative than men, (4) there is no connection between sex role portrayals and buying intentions, and (5) there is no link between buying intentions and company image.